PENGARUH HARDSKILL DAN SOFTSKILL TERHADAP KINERJA KARYAWAN - Marya Mujayana (Majalah Ekonomi, 2020)
Human Resources (HR) is the most important element in an organization. The quality of HR is also used by companies to meet the demands of increasingly high market demands. The company's productivity is built by a process that requires the basic competencies of hard skills and soft skills. The company's challenges will be even harder, because in addition to printing and building competent human resources, it must also be in accordance with market needs. PT. Kimia Farma Trading and Distribution (KFTD) Surabaya branch faces a similar challenge in increasing the productivity of its employees. This study will measure the extent of the ability of hard skills (X1) and soft skills (X2) on employee productivity (Y). The study population was employees of PT. Kimia Farma Trading and Distribution (KFTD) Surabaya branch. The results found that the ability of hard skills and soft skills significantly influence employee productivity with a value of R2 83.3%. Variable hard skills contributed 17.6% with a significance value of 0.015 <0.05. Meanwhile soft skills contributed 39.4% significance 0,000 <0.05.